Patient survival and therapeutic outcome in the UK bridge to transplant left ventricular assist device population. Issue 4 (18th August 2018) - Parameshwar, Jayan; Hogg, Rachel; Rushton, Sally; Taylor, Rhiannon; Shaw, Steven; Mehew, Jenny; Simon, Andre; MacGowan, Guy A; Dalzell, Jonathan R; Al Attar, Nawwar; Venkateswaran, Rajamiyer; Lim, Hoong Sern; et al.
Abstract : Objective: To study the survival and patient outcome in a population of UK patients supported by an implantable left ventricular assist device (LVAD) as a bridge to heart transplantation. Methods: Data on all adult patients (n=342) who received a HeartMate II or HVAD as a first long-term LVAD between January 2007 and 31 December 2013 were extracted from the UK Ventricular Assist Device (VAD) Database in November 2015. Outcomes analysed include survival on a LVAD, time to urgent listing, heart transplantation and complications including those needing a pump exchange. Results: 112 patients were supported with the Thoratec HeartMate II and 230 were supported with the HeartWare HVAD. Median duration of support was 534 days. During the study period, 81 patients required moving to the UK urgent waiting list for heart transplantation. Of the 342 patients, 85 (24.8%) received a heart transplant, this included 63 on the urgent list. Thirty-day survival was 88.9%, while overall patient survival at 3 years from LVAD implant was 49.6%. 156 patients (46%) died during LVAD support; the most common cause of death on a VAD was a cerebrovascular accident. There was no significant difference between the two devices used in any outcome. Conclusions: In a population of patients with advanced heart failure, who have a very poor prognosis, support with an implantable LVAD allowed a quarter to receive a heart transplant in a 3-year period. Overall survival of the cohort was about 50%. With improvement in technology and in post-LVAD management, it is likely that outcomes will improve further.